2010
DOI: 10.1016/j.jvs.2010.04.077
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-guided foam sclerotherapy is a safe and clinically effective treatment for superficial venous reflux

Abstract: UGFS for CEAP 2-6 SVR is associated with a low complication and retreatment rate. However, as patients are at risk of developing recurrent and new SVR they should be kept under review. Further UGFS for new or recurrent disease is simple, safe, and effective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
72
1
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(81 citation statements)
references
References 38 publications
1
72
1
2
Order By: Relevance
“…Our data consistently demonstrated that there was an improvement in symptoms after treatment and confirm findings reported by Bradbury et al 11 The portion of the questionnaire related to symptoms (VEINES-Sym) identified improvements in all nine items 45 days after treatment, with statistical significance for the following items: pain, heavy legs, swelling, burning sensation, restless legs, and throbbing (p<0.0001). The portion of the questionnaire related to quality of life (VEINES-QOL) confirmed these data, since it showed that 100% of patients reported being somewhat better (6%) or much better (94%) than one year before treatment.…”
supporting
confidence: 91%
“…Our data consistently demonstrated that there was an improvement in symptoms after treatment and confirm findings reported by Bradbury et al 11 The portion of the questionnaire related to symptoms (VEINES-Sym) identified improvements in all nine items 45 days after treatment, with statistical significance for the following items: pain, heavy legs, swelling, burning sensation, restless legs, and throbbing (p<0.0001). The portion of the questionnaire related to quality of life (VEINES-QOL) confirmed these data, since it showed that 100% of patients reported being somewhat better (6%) or much better (94%) than one year before treatment.…”
supporting
confidence: 91%
“…17,18 Foam sclerotherapy combined with SFL involves a shorter treatment time, less postoperative discomfort, and results in more rapid recovery compared with conventional GSV stripping under general anesthesia. [19][20][21] Bradbury et al 22 suggested that patients should be kept under review because they are at risk of developing recurrent and new superficial venous reflux. This denotes that sclerotherapy could be based on a dental care model; that is, the recurrent nature of VV may be analogous to the recurrent nature of dental caries.…”
Section: Discussionmentioning
confidence: 99%
“…UGFS on one side, and hook-phlebectomy on the other side represent mini-invasive treatments, which have undergone a growing diffusion as well. [22][23][24] In a recent meta-analysis , on the effectiveness of endovenous therapies for lower limb varices found, after 3 years, the estimated pooled success rates for stripping, UGFS, radiofrequency ablation, and laser therapy was 78%, 77%, 84% and 94% respectively. 25 Also in Rasmussen's randomized clinical trial at one year 5.8%, 4.8%, 16.3% and 4.8% of the GSVs were patent and refluxing in the laser, radiofrequency, foam and stripping groups respectively (P<0.001).…”
Section: Discussionmentioning
confidence: 99%